Stateczność dynamiczna porowatej powłoki walcowej - Belica, Tomasz
This disseration is devoted to nonlinear dynamic buckling analysis of a cylindical shell made of a porous material. The shell is simply supported on curvilinear edges and has been subjected to the combination of external uniform pressure and axial load. Mechanical and physical properties of the shell vary across its thickness and depend on the porosity of material. The change of Young's modulus and density is continuos and symetric of a middle surface of the shell. A nonlinear hypothesis of deformation of a plane cross section of the wall's shell is described. The components of displacement and strain are introduced. The effect of transverse shear on deformation of the transverse section has been taken into consideration. The equations of dynamic buckling of shell are formulated on the basis of the Hamilton's principle. The system of equations was approximately solved in the Bubnov-Galerkin's method. The obtained nonlinear equation of motion system was solved in the Runge-Kutta method. In this work a case of quasi-impulse of force were analysed. The comparative research of selected cases with the help of finite elements method has been carried out.
Keywords: stateczność dynamiczna; analiza nieliniowa; obciążenie złożone; materiał porowaty; powłoka walcowa